THE IMPACT OF NON-LINEAR WAVES ON OIL SPILL SPREADING IN BALIKPAPAN BAY - Aulia Puspitasari, Tirsa
The Balikpapan Bay, that located in East Kalimantan are one of the Indonesian waters that have a seaport that functions as a shipping/traffic route for various ships carrying commercial goods. The 2018’s oil spill incident in Balikpapan emerged as a valuable lesson on the importance of quick and effective mitigation. To ensure that mitigation is carried out as effectively as possible, simulating an oil spill is one of the approach that can be taken. The oil spill movement is driven by currents, winds, tides, and waves. It is often not to include wave variables in simulations, especially non-linear waves, as it is believed that the aforementioned factors effectively represent the condition of the ocean environment. In this study, using MoTuM software, we will analyze the impact of a non-linear wave factor to the hydrodynamic model. According to the results, there are differences between model scenario that use non-linear wave and thosse that do not. However, the difference is not significant due of the strong tidal current in Balikpapan Bay.